Factors associated with patient-reported midday fogging in established scleral lens wearers. Issue 6 (December 2020) - Schornack, Muriel M.; Fogt, Jennifer; Harthan, Jennifer; Nau, Cherie B.; Nau, Amy; Cao, Dingcai; Shorter, Ellen
Highlights: Midday fogging was reported by 26 % of patients in a sample of established scleral lens wearers. Midday fogging was not associated with age, sex, or race/ethnicity. Indications for scleral lens wear were not predictive of midday fogging. Neither specific lens designs (diameter or haptic design) nor care products were associated with midday fogging. Patients who reported redness or irritation with scleral lens wear more commonly reported midday fogging. Abstract: Purpose: To estimate the prevalence of patient-reported midday fogging and to identify risk factors for midday fogging. Method: A multicenter, cross-sectional study was conducted with an electronic survey that was distributed to scleral lens practitioners. The survey asked them to describe their most recently examined established scleral lens patient. Respondents provided data about patient-reported midday fogging, patient demographic characteristics, indication for lens wear, lens-wearing schedule, lens design, and care products. Results: Of the 248 survey respondents who indicated whether their patients had midday fogging, 64 (25.8 %) had patients who self-reported such issues. Midday fogging was not associated with demographic characteristics (age, sex, race/ethnicity), indications for scleral lens wear, mean lens diameter ( P = .30), haptic design ( P = .29), use of a daily cleaner ( P = .12), disinfection/storage solution used ( P = .71), or filling solution ( P = .65). Patients who reported midday fogging more commonly reported redness or irritation associated with scleral lens wear compared with those who did not experience midday fogging ( P = .03). Conclusions: Prevalence of midday fogging in this study was similar to previously reported rates. No specific lens design or care product was associated with patient-reported midday fogging. If inflammatory mediators are elevated in the postlens fluid reservoir of patients with midday fogging, as previously described, the redness or irritation associated with scleral lens wear suggests that ocular surface inflammation may be contributing to this phenomenon.